2019
DOI: 10.1186/s12877-019-1391-9
|View full text |Cite
|
Sign up to set email alerts
|

Falls and risk factors of falls for urban and rural community-dwelling older adults in China

Abstract: BackgroundFalls among older people have become a public health concern due to serious health consequences. Despite abundant literature on falls in older people, little is known about the rural-urban differentials in falls among older people in China. This research fills the voids of prior literature by investigating falls and the associated risk factors among Chinese seniors, with a particular focus on the rural-urban differences.MethodsData are from the 2010 wave of Chinese Longitudinal Survey on Urban and Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
38
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 33 publications
(25 reference statements)
12
38
2
1
Order By: Relevance
“…In our sample, 22.9% of the older people were aged ≥75 years. According to the data from Chinese Longitudinal Survey on Urban and Rural Elderly, the proportion of rural elderly people > 75 years old was 46.7%, which indicated a relatively older age structure [4]. Our results manifested that cognitive frailty was positively associated with falls among rural older adults in Shandong, China, in agreement with previous studies [7,8].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our sample, 22.9% of the older people were aged ≥75 years. According to the data from Chinese Longitudinal Survey on Urban and Rural Elderly, the proportion of rural elderly people > 75 years old was 46.7%, which indicated a relatively older age structure [4]. Our results manifested that cognitive frailty was positively associated with falls among rural older adults in Shandong, China, in agreement with previous studies [7,8].…”
Section: Discussionsupporting
confidence: 90%
“…These findings suggested that rural older adults are more likely to fall than urban elderly people. A study by Zhang et al [4] indicated that a higher socioeconomic status significantly reduces the odds of falls. Another reason may be that most of the rural older adults performed agricultural work, increasing the possibility of falling outdoors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While, the most common area of indoor falls were in the kitchen, bedroom and living room 7 . Indoor falls were reported more likely to occur in the situation where older persons are undertaking their daily activities and, at this age, the body tends to become weaker and physical illness can increase the risk of falls among them 7,31 . Limitations in ADL have also been documented as linked to a higher risk of falling among older persons either outdoors or indoors 32 …”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 12 ] A study by Park et al [ 13 ] about rural region revealed that female gender and older age are risk factors for fall. In a study using data from 16,393 people over 65 in China, Zhang et al [ 14 ] compared the fall characteristics of rural and urban areas. Fall incidence was higher in rural area, and hospitalization rate due to fall was higher in urban area in this study.…”
Section: Introductionmentioning
confidence: 99%